Hawai’i-nui-akea Cousins: Ancestral Gods and Bodies of Knowledge are Treasures for the Descendants - Kame’leihiwa, Lilikala (Te Kaharoa, 2009)
This article surveys elements of Polynesian mythology, and how it threads through several cultures in the Pacific, and brought about as common perception of understanding among the various indigenous cultures of the region.